A validation strategy for in silico generated aptamers. (December 2018) - Cataldo, R.; Ciriaco, F.; Alfinito, E.
Graphical abstract: Highlights: The 3D structures of 5 different anti-Angiopoietin aptamers are produced in silico . The 3D structures are ranked by using a new indicator called "effective affinity". The affinity of an aptamer for its target is monitored by using a complex network. The resistance of the aptamer-protein complex gives insights about affinity. Abstract: The selection of high-affinity aptamers is of paramount interest for clinical and technological applications. A novel strategy is proposed to validate the reliability of the 3D structures of a group of anti- Angiopoietin-2 aptamers, produced in silico by using free software. In a previous literature these aptamers were processed both in vitro and in silico, by using an approach different from that here presented, and finally tested with a SPS experiment. Computational expectations and experimental outcomes did not agree. The procedure here proposed consists of three steps: a. the production of a large set of conformations for each candidate aptamer; b. the rigid docking upon the receptor; c. the topological and electrical characterization of the products. Steps a. and b. allow a global binding score of the ligand-receptor complexes based on the distribution of the "effective affinity", i.e. the sum of the conformational and the docking energies. Step c. employs a complex network approach (Proteotronics) to characterize the electrical properties of the aptamers and the ligand-receptor complexes. Finally, the results are discussed and compared with the literature on the same aptamers. The computational predictions are in good agreement with the known experimental measurements.